2005
DOI: 10.1111/j.1525-1497.2005.40158.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of U.S. Citizenship status on cancer screening among immigrant women

Abstract: Objectives: We evaluated the relationship between U.S. citizenship status and the receipt of Pap smears and mammograms among immigrant women in California. Design: Cross‐sectional study using data from the 2001 California Health Interview Survey. Patients/Participants: Noninstitutionalized, civilian women, aged 18 years and older living in California. Measurements And Main Results: We analyzed data from the 2001 California Health Interview Survey and used logistic regression models to adjust for sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 49 publications
3
79
0
2
Order By: Relevance
“…However, women in the control group were more likely to have health insurance and a healthcare provider, factors that have been positively associated with screening in previous studies. 20,21 Given that the control group had a greater proportion of women with health insurance and a regular healthcare provider, these baseline differences may have actually attenuated the intervention effect somewhat. On the other hand, it has been suggested that having health insurance and a regular source of healthcare could have contributed to lower screening rates in the control group if insurance companies are unwilling to cover the costs of annual screening or if physicians are recommending longer screening intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, women in the control group were more likely to have health insurance and a healthcare provider, factors that have been positively associated with screening in previous studies. 20,21 Given that the control group had a greater proportion of women with health insurance and a regular healthcare provider, these baseline differences may have actually attenuated the intervention effect somewhat. On the other hand, it has been suggested that having health insurance and a regular source of healthcare could have contributed to lower screening rates in the control group if insurance companies are unwilling to cover the costs of annual screening or if physicians are recommending longer screening intervals.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] It is well established that women who do not have health insurance or lack a regular source of healthcare are less likely to receive a Pap test than women who have insurance or a primary care provider. 20,21 Although there are a number of programs available that provide low-cost or free cancer-screening services, Chinese American women are often unaware of these services or face considerable barriers to accessing such programs. Therefore, in this medically underserved population, there is a need to develop comprehensive approaches to help women obtain cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study evaluated the relationship between U.S. citizenship status and the receipt of Pap smears among immigrant women in this study California Citizen immigrants were significantly more likely to report receiving a Pap smear ever (adjusted prevalence ratio [aPR], 1.05; 95% confidence interval [CI], 1.01 to 1.08), a recent Pap smear (aPR, 1.07; 95% CI, 1.03 to 1.11) as compared to immigrants who are not U.S. citizens (DE Alba, 2005).. Also variables like income, having a usual source care, and having health insurance were associated with receiving cancer screening. This study showed Hispanic women were more likely to receive Pap smears as compared to whites and Asians (DE Alba, 2005). Foreign birthplace may explain some disparities previously attributed to race or ethnicity, and is an important barrier to cancer screening, even after adjustment for other factors.…”
Section: Other Variablesmentioning
confidence: 95%
“…Access barriers, including cost of screening, lack of insurance, and language difficulties, pose formidable challenges and are the most often cited factors influencing screening behavior (9,11,13). It is well established that women who do not have health insurance or lack a regular source of healthcare are less likely to receive a Pap test than women who have insurance or a primary care provider (9,15). In addition, poor English language proficiency is a key barrier to obtaining screening (7).…”
Section: Introductionmentioning
confidence: 99%